The Case for an Arctic Region Council and a Treaty Proposal - Pharand, Donat (Revue générale de droit, 1992)
In the first part of this study, the author brings out the need for an Arctic Region Council by examining what would be its main purposes. These would be to facilitate cooperation generally among its members and, in particular, with respect to the following matters: protection of the environment, coordination of scientific research, conservation of living resources, economic development, health and well-being of the Arctic inhabitants, and peaceful uses of the Arctic.The second part outlines the main reasons for the establishment of a Council by the conclusion of a treaty and presents the basic draft provisions of such treaty. These would cover: the geographical area of the Council's activities, the purposes of the Council, the conditions of membership, the main organs of the Council and their respective powers and mode of operation, the holding of meetings, the sharing of expenses, the settlement of disputes, the manner of entry into force, and the procedure of amendments and review. The founding Members of the Council would be the eight States whose territory projects north of the Arctic Circle: Canada, Denmark, Finland, Iceland, Norway, Russia, Sweden and the United States. Membership would be open to non-Arctic States having demonstrated a sufficient interest in Arctic issues, as well as to certain non-State entities such as the Northwest Territories and Greenland, and non-governmental organizations such as the Arctic Aboriginal Conference.